PENGARUH MIKORIZA TERHADAP PENYAKIT LAYU BAKTERI (Ralstonia solanacearum) PADA TANAMAN TOMAT (Licopersicum esculentum) - Kolo, Maria Serliana; Hahuly, Mayavira Veronica; Iburuni, Yohanes U. R.; Serangmo, Diana Y. L. (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Tomato plays an important role in Indonesian agriculture. Tomato production has been constrained by diseases, one of which was bacterial wilt (Ralstonia solanacearum). Application of Vesicular Arbuscular Mycorhiza (VAM) has been reported to be effective in suppressing diseases and can improve plant growth. This study was aimed to test the effect of VAM Glomus sp. in suppressing bacterial wilt disease on tomato (Lycopersicum esculentum). This research was conducted at Plant Disease Laboratory and Screenhouse of Agriculture Faculty, Nusa Cendana University. Seven treatments with three replications were arranged in Randomized Completely Block Design experiment. The treatments were 5 grams, 10 grams, and 15 grams of Glomus sp. per polybag that applied 1-week before pathogen inoculation, and also 5 grams, 10 grams, and 15 grams of Glomus sp. per polybag that applied simultaneously with pathogen inoculation. Control treatment was only inoculated with the pathogen. Three polybags, with two tomato plants planted in each were considered as one experimental unit. Ralstonia solanacearum was isolated from diseased tomato plant. Isolate pathogenicity was confirmed through hypersensitivity test on tobacco plants and on 21 day-old tomato plants. Two-week old tomato plants were inoculated with 15mL of suspension. The stem was punctured with sterile needle pryor inoculation. The result showed that Glomus sp. application before pathogen icoculation lowered disease incidence significantly. Application of 15 grams Glomus sp. before pathogen inoculation caused the greatest mycorrhizal vesicle formation in tomato root, which might also increased plant height and the number of leaves significantly.